Rubens, Vel?uez, and the King of Spain - Silver, Larry (Taylor and Francis, 2014)
Cover -- Title Page -- Copyright Page -- Table of Contents -- List of Illustrations -- Acknowledgments -- Introduction -- 1 Through the Veils of Pleasant Fictions -- 2 Civilization and its Malcontents -- 3 In the Empire of Eros -- 4 Heroes' Quests and Conquests -- 5 The Powers and Limits of Art -- 6 Fateful Figures -- 7 Enter Velázquez-The Philosophical Quartet -- 8 The Contemplative Mars -- 9 Servants and Masters -- 10 Hunts and the Closing of the Circle -- Conclusion: Forms of Visual Rhetoric -- Bibliography -- Index